AYURVEDIC MANAGEMENT OF PLAQUE PSORIASIS- A CASE STUDY - Sinimol T P,; Emy Surendran,; Meghna P P, (International Journal of Ayurveda and Pharma Research, 2019)
Psoriasis is a chronic, multisystem inflammatory disease with predominantly skin and joint involvement. In Ayurveda all skin diseases are described under the umbrella of Kushtha. Ayurvedic system of medicine is giving good results in management of Psoriasis. Repeated Samshodhana (purificatory therapies) along with Samshamana (palliative therapies) is the main line of treatment if skin diseases in Ayurveda. Three assessments were taken before and after treatment on scoring of Dermatology Life Quality Index (DLQI), Psoriasis Disability Index (PDI) and PASI score. Score of the patient was 63.3% before treatment and 13.3% after treatment and 3.3% after follow up on Dermatology Life Quality Index (DLQI), 44.4% before treatment and 15.5% after treatment and 5.3% after follow up on Psoriasis Disability Index (PDI) and 24.5% before treatment, 5.1% after treatment and 1.2% after follow up in PASI (Psoriasis Area and Severity Index).  This case study wants to substantiate the effectiveness of Ayurvedic treatment in the management of Plaque psoriasis.